Computational investigation of effects of UP state on EPSP in striatal Medium Spiny Neurons - Mrunal, Rane; Aagam, Shah; Shivani, Sheth; Rohit, Manchanda, Prof (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/